Vocalismos em narrativas orais nas trilhas do filologia Bandeirante - (:unkn) unknown (Universidade Federal de Goiás, 2017)
This dissertation presents the results of the research "Vocalisms in oral narratives in the tracks of the Bandeirante Philology", which had as corpus four narratives that are part of the first CD of the Project entitled Bandeirante Philology . These refer to the older subjects of the States of Goiás, São Paulo and Minas Gerais, taking into account that the CD does not include the federative state of Mato Grosso. The general objective of this research was to verify the vowel morphophonological processes performed by these narrators, considering the linguistic and social factors. As specific objectives, we can list: a) to describe and classify the processes that occur at the vocal level; B)to verify the most and least recurrent in each State; C) to confront the data, in order to point out the convergent and divergent processes between the narratives. The hypothesis of this work is that there are remnants of the language used by the bandeirantes in the speeches of subjects over sisty years old of the federative states mentioned, with no or very low degree of formal education and with little or no access to mass culture, lean to mantain more linguistic traits of a prior speech than younger speakers. To accomplish what was proposed, the corpus was transcribed graphically to obtain the data that were later transcribed phonetically. The graphic transcript aims to enable the general consultants to understand the narratives without great difficulties. On the other hand, the phonetic transcription had as an intention to uncover peculiarities of the pronunciations of the words. A posteriori, the processes of vocalisms realized in each narrative were identified, separating them by narrators, which were sistemized by vocabulary in the Frequency and Occurrences Index. The next step consisted of the analysis of the greater or lesser productivity of the processes, according to the profile of each narrator. With the aim of basing the stages that culminated in the analysis, we use theories of Phonetics, Phonology, Morphology, Historical Linguistics, Sociolinguistics, amidst others of related disciplines, such as Mattos e Silva (2008), Faraco (2005), Alkmin 2008, 2011), Callou and Leite (2003), among others. The results showed that there is a continuum between the processes of vocalisms in the narratives of each federative state that is part of the route of the bandeirantes, which can be considered remnants of their speeches, as attested by the historiography of the language (cf. MEGALE, 2000), although there are no oral records of the language spoken by them
Vocalisms in oral narratives in the steps of the Bandeirante philology
Keywords: Processos morfofonológicos; Vocalismos; Narrativas orais; Morphophonological processes; Vocalisms; Oral narratives; LINGUISTICA, LETRAS E ARTES::LINGUISTICA